2015
DOI: 10.1590/0004-282x20150078
|View full text |Cite
|
Sign up to set email alerts
|

Validation and cross-cultural adaptation of sexual dysfunction modified scale in multiple sclerosis for Brazilian population

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS). These patients suffer from various comorbidities, including sexual dysfunction (SD). The lesions of MS may affect regions of the CNS along the pathway of sexual response. The Multiple Sclerosis Intimacy and Sexuality Questionnaire-19 (MSISQ-19) is a scale that assesses sexual dysfunction. Adapt and validate the MSISQ-19 to Brazilian patients with MS. 204 individuals were evaluated, 134 patients with MS and 70 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
(15 reference statements)
6
17
1
Order By: Relevance
“…Case‐control studies demonstrated that SD was more commonly reported in MS compared to healthy controls . There were 14 case‐control studies exploring SD in PwMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case‐control studies demonstrated that SD was more commonly reported in MS compared to healthy controls . There were 14 case‐control studies exploring SD in PwMS.…”
Section: Discussionmentioning
confidence: 99%
“…Results of case-control studies (n = 14): The prevalence of SD in women with MS was reported to be 34.9% to 95% (n = 8 studies). In these studies, SD rates were reported to be higher in PwMS compared to healthy control [45][46][47][48][49][50][51][52][53] and the difference was found to be statistically significant in eight studies [45][46][47][48][49][50][51]53 (Table S1). No significant differences in prevalence were seen compared with other chronic neurological disorders (migraine).…”
Section: Prevalence and Symptomatology Of Sdmentioning
confidence: 99%
“…It is a valid and reliable short version of the MSISQ-19 and consists of 15 items. The MSISQ-15 is divided in three dimensions to allow focus on the specific domain of sexual concerns; primary SD (items 8, 12, 13, 14, 15), secondary SD (items 1, 2, 3, 4, 5), and tertiary SD (items 6,7,9,10,11). Each item is rated on a five-point Likert scale ranging from 0 (never) to 5 (always).…”
Section: Questionnairesmentioning
confidence: 99%
“…Tertiary SD refers to the psychological, emotional, social, and cultural aspects of MS that impact sexual function . The original version of the MSISQ was in English and consisted of 19 items and has been translated and validated in the Persian and Portuguese languages . A re‐evaluation in a larger English cohort resulted in a validated 15 item version …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation